2017
DOI: 10.1016/j.conb.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Glial contributions to neuronal health and disease: new insights from Drosophila

Abstract: Glial cells are essential for proper formation and maintenance of the nervous system. During development, glia keep neuronal cell numbers in check and ensure that mature neural circuits are appropriately sculpted by engulfing superfluous cells and projections. In the adult brain, glial cells offer metabolic sustenance and provide critical immune support in the face of acute and chronic challenges. Dysfunctional glial immune activity is believed to contribute to age-related cognitive decline, as well as neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…7). It is known that Drosophila astrocytes (ALG) are signi cant contributors to modulate neurotransmitter homeostasis within synapses [18] and also regulators of circadian rhythm [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). It is known that Drosophila astrocytes (ALG) are signi cant contributors to modulate neurotransmitter homeostasis within synapses [18] and also regulators of circadian rhythm [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that abolishing the functions of ALG or ALG-speci c genes could interfere with normal locomotion properties and lifespan of D. melanogaster, which are the direct outcome of dysregulations in neurotransmission and circadian rhythm, respectively. Moreover, it was recently reported that mitochondrial dysfunctions in ALG cells contribute to neurodegeneration [18,20], which could give rise to shortened lifespan of D. melanogaster [21].…”
Section: Discussionmentioning
confidence: 99%
“…7). It is known that Drosophila astrocytes (ALG) are significant contributors to modulate neurotransmitter homeostasis within synapses [23] and also regulators of circadian rhythm [24].…”
Section: Discussionmentioning
confidence: 99%
“…7). It is known that Drosophila astrocytes (ALG) are significant contributors to modulate neurotransmitter homeostasis within synapses [18] and also regulators of circadian rhythm [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that abolishing the functions of ALG or ALG-specific genes could interfere with normal locomotion properties and lifespan of D. melanogaster, which are the direct outcome of dysregulations in neurotransmission and circadian rhythm, respectively. Moreover, it was recently reported that mitochondrial dysfunctions in ALG cells contribute to neurodegeneration [18,20], which could give rise to shortened lifespan of D. melanogaster [21].…”
Section: Discussionmentioning
confidence: 99%